European conformation and fat scores of bovine carcasses are not good indicators of marbling. (December 2020) - Liu, Jingjing; Chriki, Sghaier; Ellies-Oury, Marie-Pierre; Legrand, Isabelle; Pogorzelski, Grzegorz; Wierzbicki, Jerzy; Farmer, Linda; Troy, Declan; Polkinghorne, Rod; Hocquette, Jean-François
Abstract: Marbling is one of the primary carcass attributes utilized in most beef grading systems for eating quality evaluation. In Europe, the current beef grading system is the EUROP grid, which is focused on carcass commercial value and production yield rather than eating quality estimation. The aim of this study was to investigate the relationship between marbling and the most common scores for carcass classification in Europe. If there are strong associations between marbling and European classification scores, marbling score may be estimated from the carcass characteristics. However, this study indicated that European classification scores explain only a slight proportion of the variance in marbling score (32%, 46%, 34% and 21% for the entire cattle group, young bulls, females and steers, respectively). Therefore, whereas the EUROP grid is well adapted to estimate yield, it does not reflect marbling at all. The European beef industry should take into account additional indicators related to beef palatability to assist the determination of the commercial value of carcasses. Highlights: European conformation and fatness scores of bovine carcasses are poorly related to marbling score. Estimation of marbling score is not feasible from carcass characteristics. Indicators relating to beef eating quality such as marbling should be introduced in carcass grading in Europe.